Saúde bucal no Brasil: uma nova política de enfrentamento para a realidade nacional - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Fadel, Cristina Berger [UNESP]; Bino, Lívia da Silva [UNESP] (My University, 2010)
The implement of Specialized’s Dentistry Centers in Brazil is, on present-day, one of the prime faces of Oral Health Brazilian Political, of which is to amplify and to qualify the specialized’s dentistry services proffer. The aim of this study, done with indirect dates, was to analyze the implantation and geographical distribution of these Centers in Brazil and try to make a relationship between this information and social and oral health factors. The results obtained showed the presence of 339 Centers already implanted in Brazil, homogeneously allocated in 283 cities, by a total of 5.560 brazilian cities, presented in the five Greater Regions. The most of the Centers were presented in large load cities. The data showed Southeast, Central West and Northeast regions with the major percentage of cities carrying Specialized’s Dentistry Centers (7,6%; 6,5%; 6,1%, respectively), while North and South regions present the minor covering taxes (4,0% and 4,5%, respectively). Relation to population’s social and buccal needs, North and Northeast Regions have the most adverse conditions, on the contrary to South, Southeast and Central West Regions who show the best one. Although the finded results were not so expressive, reflecting the brazilian geographical and populational characteristics and the essential development of specialized dentistry services, this initiative presents a real progress over the reorganization of dentistry’s practice.

A implantação de Centros de Especialidades Odontológicas (CEO) no Brasil constitui-se atualmente em uma das principais frentes da Política Nacional de Saúde Bucal, cujo desafio é ampliar e qualificar a oferta de serviços odontológicos especializados. Com o objetivo de analisar a implantação e a distribuição geográfica dos CEO no Brasil e relacioná- las com indicadores de saúde bucal e indicadores sociais amplos desenvolveu-se este estudo, fruto da exploração de fontes secundárias. Os resultados obtidos mostram que o Brasil conta atualmente com 339 CEO implantados, distribuídos de forma relativamente homogênea em 283 dos 5.560 municípios brasileiros, presentes nas cinco Grandes Regiões. A maioria dos CEO encontra-se implantada em municípios de grande porte. Os dados expuseram que as regiões Sudeste, Centro-Oeste e Nordeste obtêm as maiores porcentagens de municípios cobertos pelos CEO (7,6%; 6,5%; 6,1%, respectivamente), enquanto as regiões Norte e Sul apresentam as menores taxas de cobertura (4,0% e 4,5%, respectivamente). Com relação às necessidades sociais e de saúde bucal da população, as regiões Norte e Nordeste são portadoras das condições menos favoráveis, situação contrária às regiões Sul, Sudeste e Centro-Oeste que apresentam as melhores condições. Embora os resultados da implantação dos CEO no Brasil sejam ainda tímidos, frente às características geográficas e populacionais do país e à necessidade de expansão de serviços odontológicos de maior complexidade, esta iniciativa representa um avanço real na reorganização da prática odontológica.
Brazilian oral health: a new fronting politic at national reality
Keywords: Health political; Dentistry; Oral health services; Política de saúde; Odontologia; Serviços de saúde bucal